The ancient people of Balinese: a study of health status based on paleopathology remains - Rahmawati, Neni Trilusiana; Prayudi, Ashwin; Suriyanto, Rusyad Adi; Hastuti, Janatin; Aritona, Fidelis; Hidayah, Ati Rati (Anthropological Review, 2024)
Humans have been constantly exposed to the environment in their daily activities, which may result in some pathological changes. Paleopathology research is rare, particularly on ancient humans who lived in Bali, Indonesia. This research is intended to gain more insight into the history of diseases and the community in the past to assist future health researchers. This study was conducted to understand variation in disease among the ancient populations in Bali, Indonesia. The study examines skeletons from the Gilimanuk, Semawang, and Pacung Sembiran sites in Bali, Indonesia, collected from 1964 to 2008. A total of 336 individuals were identified, including 63 adult males, 75 adult females, and 56 adults whose sex could not be determined. In addition, 142 children were included in the analysis. The examination of the individuals revealed the presence of various dental pathological changes, such as caries and enamel hypoplasia, as well as periodontitis. Furthermore, several bone-related diseases and abnormalities were identified, such as osteophytes, fractures, porotic hyperostosis, and spina bifida occulta. Available evidence suggests a similarity in the types of pathological changes among the ancient populations of Gilimanuk, Semawang, and Pacung Sembiran. While a comprehensive explanation of the paleopathological variations observed in these populations necessitates further investigation, the present findings hold considerable value for medical experts and anthropologists seeking to better understand patterns of disease distribution among ancient Indonesian populations. This study was funded by the Directorate General of Higher Education, Research, and Technology of the Ministry of Education, Culture, Research, and Technology of Indonesia for the fiscal year 2023.